OLIG2 immunolabeling in feline ependymoma. (September 2022) - Demeter, Elena A.; Kent, Marc; Glass, Eric N.; Rissi, Daniel R.; Edwards, John; Miller, Andrew D.
Ependymoma, one of the most common gliomas in cats, occurs most often in the lateral and third ventricles and has variable histologic patterns that often form rosettes and pseudorosettes. Oligodendrocyte transcription factor (OLIG2) is expressed in oligodendrocyte precursor cells and mature oligodendrocytes. Although widely used as a diagnostic marker for most gliomas, OLIG2 is reported to have minimal immunolabeling in ependymomas. Here we characterize the OLIG2 immunolabeling pattern in 19 cases of feline ependymoma, which occurred predominantly in the lateral and third ventricles. Immunohistochemistry for GFAP was variable in 14 cases and was typically localized in the cytoplasmic processes of the neoplastic ependymal cells, especially in the rosettes and pseudorosettes. Nuclear OLIG2 immunolabeling was present in 17 cases and varied in intensity from weak (4 cases) to strong (13 cases). The distribution of OLIG2 immunolabeling within the neoplasms included none (2 cases), <25% (7 cases), 25–50% (6 cases), 51–75% (2 cases), and >75% (3 cases). OLIG2 immunolabeling intensity and distribution is widespread in feline ependymoma, in contrast to ependymomas in other species, and should not be relied upon as a specific marker for feline oligodendroglioma.